Health behavior and health promotion theories: application in environmental sciences and health - Njoku, Anuli; Molla, Azizur; Tohura, Sharaban (Handbook of Concepts in Health, Health Behavior and Environmental Health, 2025)
Keywords: Environmental health; Health behavior; Health promotion; Medicine; Nursing; Psychology; Public health; dept.pch

Climate Justice: Access to Safe Drinking Water and Health—A Legal Discourse - Njoku, Anuli U.; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Addressing the issues of water insecurity and unequal access to water has been a priority of the Sustainable Development Goals. Poor sanitation and inadequate access to drinking water are the second leading causes of death among children worldwide. Access to safe drinking water is a fundamental human right. Climate change represents one of public health’s greatest challenges and significantly exacerbates health disparities. According to the World Health Organization, approximately 3.6 billion people reside in areas highly vulnerable to the effects of climate change. Furthermore, climate change is anticipated to result in roughly 250,000 additional deaths each year between 2030 and 2050. In the United States, climate impacts such as severe storms and floods, escalating wildfires, extreme heat, poor air quality, and diminishing access to food and water disproportionately endanger Black, Brown, and Indigenous communities, low-income groups, people with disabilities, women, children, older adults, and others, making them more susceptible to the harmful health effects of climate change. The formulation and implementation of climate policies are essential to address the negative impacts of climate change. This chapter aims to: (a) describe the effects of climate change on access to safe drinking water; (b) emphasize the implications of climate change on drinking water disparities; (c) highlight policies to mitigate the effects of climate change; and d) discuss recommendations to tackle climate change and inequities in access to water. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Climate change; Environmental injustice; Health disparities; Water disparity; Water injustice; Water insecurities; Water scarcity; dept.pch